2022
DOI: 10.1002/ijgo.14456
|View full text |Cite
|
Sign up to set email alerts
|

Quality of maternal and newborn care in Switzerland during the COVID‐19 pandemic: A cross‐sectional study based on WHO quality standards

Abstract: Objective To explore quality of maternal and newborn care (QMNC) in healthcare facilities during the COVID‐19 pandemic in Switzerland. Methods Women giving birth in Switzerland answered a validated online questionnaire including 40 WHO standards‐based quality measures. QMNC score was calculated according to linguistic region and mode of birth. Differences were assessed using logistic regression analysis adjusting for relevant variables. Results A total of 1175 women were included in the analysis. Limitations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The IMAgiNE EURO surveys show high levels of medicalization throughout Europe, especially cesarean, instrumental births, and application of fundal pressure 1–10 . This is also coupled with lack of informed consent, lack of support for initiation and continuation of breastfeeding, and lack of respect and dignity for birthing women.…”
Section: White Ribbon Alliance (Wra)mentioning
confidence: 99%
See 2 more Smart Citations
“…The IMAgiNE EURO surveys show high levels of medicalization throughout Europe, especially cesarean, instrumental births, and application of fundal pressure 1–10 . This is also coupled with lack of informed consent, lack of support for initiation and continuation of breastfeeding, and lack of respect and dignity for birthing women.…”
Section: White Ribbon Alliance (Wra)mentioning
confidence: 99%
“…This is also coupled with lack of informed consent, lack of support for initiation and continuation of breastfeeding, and lack of respect and dignity for birthing women. The results were even worse for women who were not from the majority population—young, immigrant, or from linguistic minorities 9,10 . With the increase in medicalization, including cesarean and instrumental vaginal birth (IVB), women reported feeling that they were treated with less dignity and respect 1 .…”
Section: White Ribbon Alliance (Wra)mentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2020, the IMAgiNE EURO study, based on the WHO Standards for improving Quality of Maternal and Newborn Care (QMNC) [26], has been documenting QMNC during the COVID-19 pandemic in the European Region. Several studies resulting from this international project reported limitations in the QMNC provided during the COVID-19 pandemic [27][28][29][30]. Quantitative data from the IMAgiNE EURO study among 1′175 women who gave birth in Switzerland from March 2020 to February 2022, indicate that about 28% of women reported limitations in the QMNC during the pandemic [27].…”
Section: Introductionmentioning
confidence: 99%
“…Both TLTL and TMTS are costly for health systems and can be dangerous for women and newborns ((35). In addition, the literature indicates that women, both in low- and high-income countries (HICs) are often not adequately informed and are minimally involved in decision-making prior to conducting these interventions during childbirth ((58). Also, other aspects of experience of care such as privacy, quality of communication, respect and dignity have been described as substandard both in low and HICs (9,10).…”
Section: Introductionmentioning
confidence: 99%